A Comparison of Corneal Biomechanical Properties in Patients With Psoriasis and Healthy Subjects. Issue 2 (March 2015) - Celik, Ugur; Aykut, Veysel; Celik, Burcu; Tas, Mehmet; Yazgan, Serpil; Kaldırım, Havva; Erdur, Sevil Karaman
Abstract : Objective: To evaluate the differences in corneal biomechanical properties between healthy subjects and patients with psoriasis using the ocular response analyzer (ORA). Methods: Fifty-nine eyes of 59 psoriasis patients and 66 healthy individuals were included in the study. Corneal biomechanical parameters were obtained using ORA. Ultrasound pachymetry was used to measure central corneal thickness (CCT). The main parameters assessed were corneal hysteresis (CH), corneal resistance factor (CRF), Goldmann-correlated intraocular pressure (IOPg) measurement and corneal-compensated IOP (IOPcc) through ORA. The dry eye evaluation was performed with tear break-up time (TBUT) and Shirmer test. Results: The mean CH values in psoriasis and healthy subject eyes were 10.75±2.9 mm Hg, 11.97±3.6 mm Hg, respectively ( P =0.047). The mean CRF values were 10.14±3.1 mm Hg and 11.61±3.3 mm Hg, respectively ( P =0.012). The mean CCT were 539.1±36 μm and 536.3±28 μm, respectively ( P =0.643). Mean TBUT values were 8.2±2.9 sec in psoriasis group and 10.4±3.6 sec in healthy subjects ( P <0.001). Shirmer test values were less (8.9±3.8 mm/5 min) in psoriasis than in healthy subjects (13.1±3.6 mm) ( P <0.001). Conclusions: Psoriasis can influence the corneal biomechanical properties. Patients with psoriasis had lower CH and CRF, but higher IOPg and IOPcc values than healthy controls. These corneal biomechanical changes should be considered when determining IOP values.